Correction of gasoline blending recipes with the use of computer modelling system; IOP Conference Series: Materials Science and Engineering; Vol. 93: Modern Technique and Technologies (MTT'2015) - Kirgina M. V. Mariya Vladimirovna; Sviridova E. A. Ekaterina Andreevna; Sakhnevich B.; Chekantsev N. V. Nikita Vitalievich; Ivanchina E. D. Emilia Dmitrievna (Power industry, 2015)
Title screen